Anti-corrosive properties and quantum chemical studies of (Benzoxazol) derivatives on mild steel in HCl (1 M) - Benzai,A. (2021)
Abstract This work is a contribution to the study about the inhibition of mild steel corrosion in a molar hydrochloric acid medium by some benzoxazol derivatives compounds. The study was carried out using gravimetric and electrochemical methods (stationary and transient). We have considered the influence of the inhibitor concentration, the temperature of the medium and the duration of the immersion of the metal sample in the aggressive medium. These studies are complemented with theoretical calculations aimed to correlate the results obtained from experimental measurements using the DFT method. The results obtained in this work through gravimetric and both transient and stationary electrochemical methods showed a satisfied coherence. Theoretical calculations also revealed a good correlation with the experimental results for our compounds.